2011
DOI: 10.5606/kbbihtisas.2011.003
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular dissection versus superficial parotidectomy in pleomorphic adenomas of the parotid gland

Abstract: Objectives:We aimed to compare the results of extracapsullary dissection (ED) with superficial parotidectomy (SP) in the surgical treatment of benign parotid tumors. Patients and Methods:Forty-one patients who were diagnosed with pleomorphic adenoma of the parotid gland and underwent surgery between January 1992 and June 2000 were enrolled in this study. The patients were divided into two groups: the ED group (6 males, 15 females; mean age 47.2 years; range 32 to 57 years) and the SP group (7 males, 13 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…One of the most devastating complications in parotid surgery is recurrent disease. Especially pleomorphic adenomas that harbor a significant risk for recurrent disease with a slightly higher recurrence rates after extracapsular dissection (0% to 10%) compared with SP (0% to 6.7%; Table ) . In accordance with the literature, we found a significantly higher rate of recurrent disease after extracapsular dissection compared with SP.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One of the most devastating complications in parotid surgery is recurrent disease. Especially pleomorphic adenomas that harbor a significant risk for recurrent disease with a slightly higher recurrence rates after extracapsular dissection (0% to 10%) compared with SP (0% to 6.7%; Table ) . In accordance with the literature, we found a significantly higher rate of recurrent disease after extracapsular dissection compared with SP.…”
Section: Discussionsupporting
confidence: 89%
“…Because our department had a considerable large number of patients treated between the 1960s and 1990s, it was obvious to compare the clinical outcome and time of surgery between these 2 surgical techniques. To the best of our knowledge, this study includes the largest collective of performed SPs and the second largest collective of conducted SPs and extracapsular dissections in total (Table ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the past have found enucleation of benign tumours to be associated with an unacceptably high chance of tumour recurrence especially for pleomorphic adenomas [22]. However, several recent studies have suggested that a more limited resection in the form of extracapsular dissection where the pleomorphic adenoma is resected only with a cuff of normal glandular tissue offers better postoperative cosmetic result and lower incidence of Frey's syndrome without an increase in the incidence of tumour recurrence and facial nerve injury [2325]. Recurrence rates with either approach are in the order of 1–3% in the literature [26].…”
Section: Treatmentmentioning
confidence: 99%
“…Studies in the past have found enucleation of benign tumours to be associated with an unacceptably high chance of tumour recurrence especially for pleomorphic adenomas [22]. However, several recent studies have suggested that a more limited resection in the form of extracapsular dissection where the pleomorphic adenoma is resected only with a cuff of normal glandular tissue offers better postoperative cosmetic result and lower incidence of Frey's syndrome without an increase in the incidence of tumour recurrence and facial nerve injury [23][24][25]. Recurrence rates with either approach are in the order of 1-3% in the literature [26].…”
Section: Treatmentmentioning
confidence: 99%